1997
DOI: 10.4319/lo.1997.42.5_part_2.1215
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of grazer populations as a contributing factor to the initiation of the Texas brown tide algal bloom

Abstract: Disruption of grazer populations, or mismatches between phytoplankton blooms and population dynamics of their planktonic and benthic grazers, may play an important role in the initiation of some harmful algal blooms. The Laguna Madre of Texas has experienced a persistent, nearly monospecific phytoplankton bloom since January 1990 commonly referred to as the "brown tide." Whole-water samples collected in the area where the bloom began reveal the pattern of bloom initiation and dispersion during the first few mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
79
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 34 publications
4
79
1
Order By: Relevance
“…The bloom was formed by Aureoumbra lagunensis (Stockwell, DeYoe, Hargraves, and Johnson), a small pelagophyte that shares some similarities to the species that forms brown tides along the coast of Long Island (DeYoe et al 1997). It has been suggested that hypersaline conditions in the Laguna Madre may favor brown tide blooms (Buskey et al 1998). Several lines of evidence support this hypothesis.…”
mentioning
confidence: 49%
See 4 more Smart Citations
“…The bloom was formed by Aureoumbra lagunensis (Stockwell, DeYoe, Hargraves, and Johnson), a small pelagophyte that shares some similarities to the species that forms brown tides along the coast of Long Island (DeYoe et al 1997). It has been suggested that hypersaline conditions in the Laguna Madre may favor brown tide blooms (Buskey et al 1998). Several lines of evidence support this hypothesis.…”
mentioning
confidence: 49%
“…These findings lead us to hypothesize that the increased EPS mucus layer surrounding A. lagunensis cells may prevent effective grazing by microzooplankton. Previous studies (Buskey and Hyatt 1995) found lower growth rates of protozoa fed A. lagunensis compared to other similarly sized algal species, but the mechanism causing the reduced growth was unknown.…”
mentioning
confidence: 99%
See 3 more Smart Citations